Flood effect on tree communities in the multispecific forest at Taiamã Ecological Station (Sítio Ramsar), Pantan al Matogrossense (Research, Society and Development, 2020)
The Pantanal is part of the wetlands of international importance and undergoes seasonalfloods that result in the influence of the richness and diversity of tree and shrub species. Thus,the objective of this work was to evaluate the effect of flooding on tree communities, floristic composition and phytosociological structure in areas of polyspecific forest of the EstaçãoEcológica de Taiamã. The survey was carried out in four modules of 100x40 meters andsubdivided into smaller plots of 25x20, later the tree and shrub species were measured with CAP (circumference at breast height) greater than 15 centimeters and the total height of thetrees greater than 2 meters. To explain the patterns of species distribution in the community, aRedundancy Analysis (RDA) was performed, relating species and abundancetoenvironmental variables: quota, plots and module. 529 individuals were registered, 34 speciesdistributed in 20 botanical families. The diametric structure of the community presented the“inverted J” pattern, indicating that the forest is in balance and that natural regenerationoccurs. The total density per hectare found for the community was 440.8 ind ha-¹, the basalarea was 14.11 ± 0.81 m² / ha. The Shannon-Wiener (H ') diversity index was 2.89 and thePielou (J') equability was 0.82. The species that showed the highest Importance Value (VI)were,Inga vera Willd,Zygia inaequalis(Willd.) Pittier and Trichilia catigua A.Juss. The redundancy analysis indicates that the species are associated with the environmental gradient.